Insulin injection regimens and metabolic control in an international survey of adolescents with type 1 diabetes over 3 years: results from the Hvidore study group - Holl, Reinhard W; Swift, Peter G F; Mortensen, Henrik B; Lynggaard, Helle; Hougaard, Phillip; Aanstoot, Henk-Jan; Chiarelli, Francesco; Daneman, Denis; Danne, Thomas; Dorchy, Harry; Garandeau, Patrick; Greene, Steven; et al. (Springer, 2003)
The optimal insulin regimen for paediatric patients with type 1 diabetes remains controversial. Therefore this multicentre study was performed in adolescents over a 3-year period to assess metabolic control, severe hypoglycaemia, and weight gain in relation to insulin injection regimens. Out of 2873 children and adolescents in an international survey in 1995, 872 adolescents (433 boys, 439 girls, mean age in 1995 11.3+/-2.2 years) were restudied in 1998, relating insulin regimens to HbA(1c) measured in a central laboratory. In addition, the daily dose of insulin, changes in body mass index (BMI), and events of severe hypoglycaemia were evaluated. Over 3 years, the use of multiple injection regimens increased from 42% to 71%: 251 patients remained on twice daily insulin, 365 remained on multiple injections and 256 shifted from twice daily insulin to multiple injections. In all three subgroups an increase in insulin dose, a deterioration of metabolic control, and an increase in BMI were observed. Metabolic control deteriorated less than expected over 3 years during adolescence (HbA(1c) 1995: 8.7+/-1.6%; 1998 observed: 8.9+/-1.6%, HbA(1c) expected for 1998: 9.0%). BMI increased more than expected, the increase was greatest in patients switching from twice daily to multiple injections, and higher in females compared to males.